Difference between revisions of "008A Sample Final A, Question 16"

From Math Wiki
Jump to navigation Jump to search
 
Line 2: Line 2:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
!Foundations
+
!Foundations:  
 
|-
 
|-
 
|1) How do we combine the two logs?
 
|1) How do we combine the two logs?
Line 18: Line 18:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 1:
+
!Step 1:  
 
|-
 
|-
 
|Using one of the properties of logarithms the, left hand side is equal to <math> \log_6( (x + 2)(x - 3)</math>
 
|Using one of the properties of logarithms the, left hand side is equal to <math> \log_6( (x + 2)(x - 3)</math>
Line 24: Line 24:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 2:
+
!Step 2: &nbsp;
 
|-
 
|-
 
|By the definition of logarithms <math> \log_6( (x + 2)(x - 3) = 1</math> means <math> 6 = (x + 2)(x - 3)</math>
 
|By the definition of logarithms <math> \log_6( (x + 2)(x - 3) = 1</math> means <math> 6 = (x + 2)(x - 3)</math>
Line 30: Line 30:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 3:
+
!Step 3: &nbsp;
 
|-
 
|-
 
|Now we do some arithmetic to solve for x. <math> 0 = (x + 2)(x - 3) - 6 = x^2 - x - 12 = (x - 4)(x + 3) </math>. So there are two possible answers.
 
|Now we do some arithmetic to solve for x. <math> 0 = (x + 2)(x - 3) - 6 = x^2 - x - 12 = (x - 4)(x + 3) </math>. So there are two possible answers.
Line 36: Line 36:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 4:
+
!Step 4: &nbsp;
 
|-
 
|-
 
|We have to make sure the answers make sense in the context of the problem. Since the domain of the log function is <math> (0, \infty)</math>&nbsp; , &nbsp; -3 is removed as a potential answer.
 
|We have to make sure the answers make sense in the context of the problem. Since the domain of the log function is <math> (0, \infty)</math>&nbsp; , &nbsp; -3 is removed as a potential answer.
Line 42: Line 42:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Final Answer:
+
!Final Answer: &nbsp;
 
|-
 
|-
 
| x = 4.
 
| x = 4.

Latest revision as of 23:02, 25 May 2015

Question: Solve.

Foundations:  
1) How do we combine the two logs?
2) How do we remove the logs?
Answer:
1) One of the rules of logarithms says that
2) The definition of logarithm tells us that if , then

Solution:

Step 1:  
Using one of the properties of logarithms the, left hand side is equal to
Step 2:  
By the definition of logarithms means
Step 3:  
Now we do some arithmetic to solve for x. . So there are two possible answers.
Step 4:  
We have to make sure the answers make sense in the context of the problem. Since the domain of the log function is   ,   -3 is removed as a potential answer.
Final Answer:  
x = 4.

Return to Sample Exam